An Analysis of Students’ Difficulties in Comprehending Report Text at the Eleventh Grade of SMA Swasta Islam Terpadu Daar Al Uluum Kisaran - Susi Masniari Nasution; Anisa Sapitri; Rafika Muspita Sari (JL3T (Journal of Linguistics, Literature and Language Teaching))
This research aimed to analyze the most dominant difficulties faced by the eleventh grade students of  SMA Swasta Islam Terpadu Daar Al Uluum Kisaran in comprehending reading texts and to identify factors that triggered the obstacles. This study was a qualitative research and the subject was the eleventh grade students of SMA Swasta Islam Terpadu Daar Al Uluum Kisaran in 2020/2021 Academic Year. The techniques of data collection were test and interviews. The researchers used the technique of data analysis constructed by Miles and Huberman. The steps are first, data collection; the data were collected from the students’ test. The second is data reduction; the researchers classified and reduced the data based on the research focus. Third is data display, the researcher arranged all information and drew conclusions. Results of the research showed that15,80% students had difficulties in determining main idea  (35 incorrect answers). 14,40% students had difficulties in identifying references (32 incorrect answers), 26,60% students had difficulties in understanding vocabulary (59 incorrect answers). Furthermore, 25,20% found difficulties in making inference (56 incorrect answers)and 18,00% students had difficulties in identifying detailed information of the text which the total incorrect answer was 40. The factors causing the difficulties were problems in understanding vocabulary, home and school environments, and students’ lack of learning English.